Telemonitoring of Water Quality for Koi Fish Hatchery Using Mechanical Turbine Method Based on Microcontroller - Shavira Adianda Adianda; Farida Arinie; Azzam Muzakhim Imammuddien (Politeknik Negeri Malang, 2022)
One way to meet the needs of fish seeds in the general public is to cultivate fish species. UPT BBI (Balai Benih Ikan) Tlogowaru, is one of the fish seed cultivation sites located on Tajinan Tlogowaru, Kedungkandang sub-district, Malang City. Fish seeds include koi fish seeds. In the pool using water from the river. To maintain the water of the koi fish hatchery, the condition of color turbidity is monitored as the level of turbidity of the water visible from above the waters of the koi fish hatchery, and a water flow sensor is processed by esp32. The water flows through the gravity pipe which will turn the turbine. With the rotation, the generator will produce power which is used to activate the telemonitoring device. The water then enters the filtration and will be channeled to the koi fish hatchery. The results of this study have an average pH value of 6.8 - 7.2 and a TDS of 257-282 ppm after water filtration with the turbine speed value being influenced by water flow and turbine rotation speed and the average power consumption generated for system performance of 8.265 w/h using a MiFi network with QoS parameters measured are delay and packet loss in the low category. And the use of the website makes it easier for users to monitor fish seed ponds